2005
DOI: 10.1105/tpc.105.036640
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHATE TRANSPORTER TRAFFIC FACILITATOR1 Is a Plant-Specific SEC12-Related Protein That Enables the Endoplasmic Reticulum Exit of a High-Affinity Phosphate Transporter in Arabidopsis  [W]

Abstract: PHOSPHATE TRANSPORTER1 (PHT1) genes encode phosphate (Pi) transporters that play a fundamental role in Pi acquisition and remobilization in plants. Mutation of the Arabidopsis thaliana PHOSPHATE TRANSPORTER TRAFFIC FACILITA-TOR1 (PHF1) impairs Pi transport, resulting in the constitutive expression of many Pi starvation-induced genes, increased arsenate resistance, and reduced Pi accumulation. PHF1 expression was detected in all tissues, particularly in roots, flowers, and senescing leaves, and was induced by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
255
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(269 citation statements)
references
References 58 publications
12
255
1
1
Order By: Relevance
“…5, A and B). The ER location of PHF1 has been confirmed in Arabidopsis (Gonzalez et al, 2005;Bayle et al, 2011). Our data showed that OsPHF1 is also located in ER (Fig.…”
Section: Osphf1 Regulates the Plasma Membrane Localization Of Low-andsupporting
confidence: 61%
See 2 more Smart Citations
“…5, A and B). The ER location of PHF1 has been confirmed in Arabidopsis (Gonzalez et al, 2005;Bayle et al, 2011). Our data showed that OsPHF1 is also located in ER (Fig.…”
Section: Osphf1 Regulates the Plasma Membrane Localization Of Low-andsupporting
confidence: 61%
“…One PCR product (597 bp) was obtained from Osphf1-1 and two PCR products (597 and 216 bp) were obtained from the complementation lines. The primers are listed in Supplemental Table S1 It has been suggested that AtPHF1 may be regulated by AtPHR1 (At3g52190; Gonzalez et al, 2005). To determine whether OsPHF1 is regulated by OsPHR2, a functional rice homolog of AtPHR1 (Zhou et al, 2008), plants overexpressing OsPHR2 in a phf1-1 background (designated as phf1-1;OvPHR2) were developed by crossing the phf1-1 mutant with transgenic plants overexpressing OsPHR2 (Zhou et al, 2008).…”
Section: Osphf1 Regulates the Plasma Membrane Localization Of Low-andmentioning
confidence: 99%
See 1 more Smart Citation
“…The fugu5-1 through -3 mutants as well as fugu5-1 PromAVP1:IPP1 #8-3 were previously described (Ferjani et al, 2011). The phr1 phl1 double mutant was also previously described (González et al, 2005;Bustos et al, 2010) …”
Section: Plant Materials and Transformationmentioning
confidence: 99%
“…Our findings pave the way for identification of cytosolic EAP3 interactors and for characterising the precise functions of the EAP3 protein domains during PEN3 exit from the ER. Interestingly, the ER accessory protein AUXIN RESISTANT4 and the PHOSPHATE TRANSPORTER TRAFFIC FACILITATOR1 protein, both unrelated to EAP3, mediate trafficking of specific cargos from the ER 19,20 , although the underlying molecular mechanisms remain unknown. These examples highlight future opportunities in studying molecular mechanisms underlying ER exit of specific cargos involved in important physiological processes such as hormone or phosphate transport, and disease resistance in plants, to understand the physiological relevance of such specificity.…”
mentioning
confidence: 99%